Perovskite solar cell and solar cell system
Patent Information
- Application Number
- CN202211735513.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-31
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-12-31
AI Technical Summary
[0004]本申请的主要目的在于提供一种钙钛矿太阳能电池以及太阳能电池系统,以解决现有技术中钙钛矿太阳能电池的转换效率较低的问题
[0015]应用本申请的技术方案,在本申请的钙钛矿太阳能电池中,通过在第一电极层和吸光层之间设置包括沿远离第一电极层方向电子能级依次递增的多个叠层子层的电子传输层,形成一种“阶梯式”能级结构,相比采用二氧化钛作为电子传输层,本申请可以减少电子传输势垒,减少电子传输所需能量,改善钙钛矿太阳能电池结构中的电子传输,从而提高钙钛矿太阳能电池的光电转化效率。
Smart Images

Figure CN115955850B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cells, and more specifically, to a perovskite solar cell and a solar cell system. Background Technology
[0002] The current fabrication process for perovskite solar cells is as follows: First, an electron transport layer is spin-coated onto FTO (Fluorine-Doped Tin Oxide) conductive glass. Next, a perovskite layer is spin-coated onto the perovskite layer. Then, a hole transport layer is spin-coated onto the perovskite layer. Finally, a metal electrode is vacuum-deposited. The electron transport layer can transport photogenerated electrons from the perovskite layer to the ITO (Indium Tin Oxide) electrode and blocks the transport of photogenerated holes.
[0003] However, in the existing technology, the conversion efficiency of perovskite solar cells using titanium dioxide as the electron transport layer is relatively low. Summary of the Invention
[0004] The main objective of this application is to provide a perovskite solar cell and a solar cell system to solve the problem of low conversion efficiency of perovskite solar cells in the prior art.
[0005] To achieve the above objectives, according to one aspect of this application, a perovskite solar cell is provided, comprising a first electrode layer, an electron transport layer, and a light-absorbing layer, wherein the electron transport layer is located on the surface of the first electrode layer, the electron transport layer comprises a plurality of stacked sublayers, and the electronic energy levels of the plurality of sublayers increase sequentially in a direction away from the first electrode layer; the light-absorbing layer is located on the surface of the electron transport layer away from the first electrode layer, and the material of the light-absorbing layer comprises perovskite.
[0006] Optionally, there are three sub-layers, namely a first sub-layer, a second sub-layer, and a third sub-layer stacked sequentially along the direction away from the first electrode layer.
[0007] Optionally, the electronic energy level of the first sublayer is -4.18 eV, the electronic energy level of the second sublayer is -4.05 eV, and the electronic energy level of the third sublayer is -3.95 eV.
[0008] Optionally, the material of the first sublayer includes titanium dioxide, the material of the second sublayer includes strontium titanate, and the material of the third sublayer includes titanium dioxide and graphene quantum dots.
[0009] Optionally, the first sublayer is a titanium dioxide layer, the second sublayer is a strontium titanate layer, and the third sublayer is a mixed material layer of titanium dioxide and graphene quantum dots.
[0010] Optionally, in the third sublayer, the mixing ratio of the graphene quantum dots to the titanium dioxide ranges from 1:4 to 1:10.
[0011] Optionally, the perovskite solar cell further includes a hole transport layer and a second electrode layer, wherein the hole transport layer is located on the surface of the light-absorbing layer away from the electron transport layer; and the second electrode layer is located on the surface of the hole transport layer away from the light-absorbing layer.
[0012] Optionally, the hole transport layer is made of spiro-MeOTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene), and the second electrode layer is made of at least one of gold and silver.
[0013] Optionally, the material of the first electrode layer includes at least one of FTO conductive glass and ITO conductive glass.
[0014] According to another aspect of this application, a solar cell system is provided, including any of the perovskite solar cells described above.
[0015] By applying the technical solution of this application, in the perovskite solar cell of this application, an electron transport layer comprising multiple stacked sub-layers with sequentially increasing electronic energy levels along the direction away from the first electrode layer is provided between the first electrode layer and the light-absorbing layer, forming a "stepped" energy level structure. Compared with using titanium dioxide as the electron transport layer, this application can reduce the electron transport barrier, reduce the energy required for electron transport, improve electron transport in the perovskite solar cell structure, and thus improve the photoelectric conversion efficiency of the perovskite solar cell. Attached Figure Description
[0016] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:
[0017] Figure 1 A schematic diagram of a perovskite solar cell structure according to an embodiment of this application is shown;
[0018] Figure 2 A schematic diagram of the energy level distribution of a perovskite solar cell according to an embodiment of this application is shown;
[0019] Figure 3 A schematic diagram of the complete structure of a perovskite solar cell according to an embodiment of this application is shown.
[0020] The above figures include the following reference numerals:
[0021] 100. First electrode layer; 101. Electron transport layer; 1011. First sublayer; 1012. Second sublayer; 1013. Third sublayer; 102. Light-absorbing layer; 103. Hole transport layer; 104. Second electrode layer. Detailed Implementation
[0022] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.
[0023] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative effort should fall within the scope of protection of the present application.
[0024] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate for the embodiments of this application described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0025] It should be understood that when an element (such as a layer, film, region, or substrate) is described as being "on" another element, the element may be directly on the other element, or there may be an intermediate element present. Furthermore, in the specification and claims, when an element is described as being "connected" to another element, the element may be "directly connected" to the other element, or "connected" to the other element via a third element.
[0026] As described in the background section, the conversion efficiency of perovskite solar cells in the prior art is low. To solve the above problems, embodiments of this application provide a perovskite solar cell and a solar cell system.
[0027] According to a typical embodiment of this application, a perovskite solar cell is provided, such as... Figure 1As shown, the perovskite solar cell includes a first electrode layer 100, an electron transport layer 101, and a light-absorbing layer 102. The electron transport layer 101 is located on the surface of the first electrode layer 100 and includes multiple stacked sublayers. The electronic energy levels of the multiple sublayers increase sequentially in the direction away from the first electrode layer. The light-absorbing layer 102 is located on the surface of the electron transport layer 101 away from the first electrode layer 100, and the material of the light-absorbing layer 102 includes perovskite.
[0028] The perovskite solar cell described above in this application forms a "stepped" energy level structure by including an electron transport layer comprising multiple stacked sub-layers that increase sequentially in the direction away from the first electrode layer. This reduces the electron transport barrier, makes the energy level difference between the electron transport layer and the light-absorbing layer smaller, improves electron transport in the perovskite solar cell structure, and ultimately improves the conversion efficiency of the perovskite solar cell.
[0029] Among the aforementioned sub-layers, the electronic energy level of the sub-layer in contact with the first electrode layer is higher than that of the first electrode layer, and the electronic energy level of the sub-layer in contact with the light-absorbing layer is lower than that of the light-absorbing layer.
[0030] In practical applications, the electronic energy level of the first electrode layer of this application is -4.50 eV, and the electronic energy level of the light-absorbing layer is -3.80 eV.
[0031] Furthermore, in this application, the energy difference of the electronic energy levels between the sublayer in contact with the first electrode layer and the first electrode layer is a first value. In the prior art, the energy difference of the electronic energy levels between the first electrode layer and the electron transport layer made of titanium dioxide is a second value, and the first value is less than the second value. In this application, the energy difference of the electronic energy levels between the sublayer in contact with the light-absorbing layer and the light-absorbing layer is a third value. In the prior art, the energy difference of the electronic energy levels between the light-absorbing layer and the electron transport layer made of titanium dioxide is a fourth value, and the third value is less than the fourth value.
[0032] Specifically, such as Figure 1As shown, the electron transport layer 101 comprises multiple stacked sublayers, specifically three sublayers: a first sublayer 1011, a second sublayer 1012, and a third sublayer 1013, stacked sequentially away from the first electrode layer. In this application, the electronic energy level of the second sublayer is higher than that of the first sublayer, and the electronic energy level of the third sublayer is higher than that of the second sublayer. By setting three sublayers with progressively increasing electronic energy levels between the first electrode layer and the light-absorbing layer, the matching of energy level structures between the first electrode layer and the electron transport layer, and between the electron transport layer and the light-absorbing layer, is further achieved. This further ensures a lower electron transport barrier, reduces the energy required for electron transport in the perovskite solar cell structure, and further ensures higher cell conversion efficiency.
[0033] More specifically, such as Figure 2 As shown, in one embodiment of this application, the electronic energy level of the first sublayer is -4.18 eV, the electronic energy level of the second sublayer is -4.05 eV, and the electronic energy level of the third sublayer is -3.95 eV.
[0034] It should be noted that, as Figure 2 As shown, in another embodiment of this application, the electronic energy level of the first electrode layer is -4.50 eV, the electronic energy level of the first sublayer is -4.18 eV, the electronic energy level of the second sublayer is -4.05 eV, the electronic energy level of the third sublayer is -3.95 eV, the electronic energy level of the light-absorbing layer is -3.80 eV, the electronic energy level of the hole transport layer is -2.6 eV, the hole energy level of the first sublayer is -7.38 eV, the hole energy level of the second sublayer is -7.13 eV, the hole energy level of the third sublayer is -7.13 eV, and the hole energy level of the light-absorbing layer is -5.30 eV. The hole energy level is the energy level used for hole transport.
[0035] According to an optional embodiment, the material of the first sublayer of this application includes titanium dioxide, the material of the second sublayer includes strontium titanate, and the material of the third sublayer includes titanium dioxide and graphene quantum dots. In the third sublayer of this application, the presence of graphene quantum dots reduces the reaction between hydroxyl groups and methylamine ions on the surface of titanium dioxide, avoiding loss of the light-absorbing layer and thus further improving the stability of the perovskite solar cell described in this application.
[0036] In the embodiments of this application, the first sublayer is a titanium dioxide layer, the second sublayer is a strontium titanate layer, and the third sublayer is a hybrid material layer of titanium dioxide and graphene quantum dots. This application introduces an electron transport layer comprising a titanium dioxide layer, a strontium titanate layer, and a hybrid material layer of titanium dioxide and graphene quantum dots into the perovskite solar cell structure, forming a "stepped" energy access structure, reducing the electron transport barrier, and thereby improving the cell's conversion efficiency.
[0037] Specifically, through experiments, the optimal photoelectric conversion efficiency of the perovskite solar cell employing the electron transport layer of this application can reach 21.83%. The presence of the aforementioned titanium dioxide layer, strontium titanate layer, and the mixed material layer of titanium dioxide and graphene quantum dots forms a "stepped" energy level structure, reducing the electron transport barrier between layers. This results in a more matched energy level structure in the perovskite solar cell of this application, reducing the probability of carrier recombination. Compared to traditional perovskite solar cells, the photoelectric conversion efficiency of the perovskite solar cell of this application is improved by 20%.
[0038] To further ensure the stability of the perovskite solar cell described in this application, the mixing ratio of graphene quantum dots to titanium dioxide in the third sublayer ranges from 1:4 to 1:10. The mixed material layer of titanium dioxide and graphene quantum dots formed within this mixing ratio range can reduce the reaction between hydroxyl groups and ammonium ions on the titanium dioxide surface, thereby slowing down the degradation and decomposition of the perovskite solar cell and improving its stability. Furthermore, through multiple experiments, the perovskite solar cell described in this application can still maintain 70% of its original efficiency after being placed under 50% humidity for 250 hours.
[0039] In one embodiment, the battery performance parameters of the battery obtained by applying the perovskite solar cell structure described above are shown in Table 1:
[0040] Table 1
[0041]
[0042] According to another specific embodiment of this application, such as Figure 3 As shown, the perovskite solar cell described in this application further includes a hole transport layer 103 and a second electrode layer 104. The hole transport layer 103 is located on the surface of the light-absorbing layer 102 away from the electron transport layer 101; the second electrode layer 104 is located on the surface of the hole transport layer 103 away from the light-absorbing layer 102. The hole transport layer allows photogenerated holes generated in the light-absorbing layer to be transported to the second electrode layer, while blocking the entry of photogenerated electrons, thus further realizing the function of converting solar energy into electrical energy.
[0043] In addition, such as Figure 2As shown, the hole energy level of the hole transport layer in this application is -5.24 eV.
[0044] Specifically, the material of the hole transport layer in this application includes spiro-MeOTAD, and the material of the second electrode layer includes at least one of gold and silver.
[0045] In the embodiments of this application, the material of the hole transport layer is spiro-MeOTAD, and the material of the second electrode layer is metallic gold or metallic silver.
[0046] It should be noted that the material of the first electrode layer mentioned above in this application includes at least one of FTO conductive glass and ITO conductive glass.
[0047] In a more specific embodiment, the material of the first electrode layer is FTO conductive glass or ITO conductive glass.
[0048] According to another typical embodiment of this application, a method for fabricating a perovskite solar cell is provided, the method comprising:
[0049] Step S10: Provide a first electrode layer, wherein the first electrode layer comprises at least one of FTO conductive glass and ITO conductive glass;
[0050] More specifically, this application uses acetone and ethanol to clean FTO conductive glass or ITO conductive glass, then dries and oxidizes it with ozone for 30 minutes to obtain the first electrode layer.
[0051] Step S20: An electron transport layer is formed on the exposed surface of the first electrode layer. The electron transport layer includes a plurality of stacked sub-layers, and the electron energy levels of the plurality of sub-layers increase sequentially in the direction away from the first electrode layer.
[0052] Step S30: A light-absorbing layer is formed on the surface of the electron transport layer away from the first electrode layer, and the material of the light-absorbing layer includes perovskite.
[0053] In this application, there are three sub-layers, namely a first sub-layer, a second sub-layer, and a third sub-layer stacked sequentially along the direction away from the first electrode layer.
[0054] In a more specific embodiment, the electronic energy level of the first sublayer is -4.18 eV, the electronic energy level of the second sublayer is -4.05 eV, and the electronic energy level of the third sublayer is -3.95 eV.
[0055] The material of the first sublayer of this application includes titanium dioxide, the material of the second sublayer includes strontium titanate, and the material of the third sublayer includes titanium dioxide and graphene quantum dots.
[0056] As can be seen from the materials of the three sub-layers mentioned above, the first sub-layer of this application is a titanium dioxide layer, the second sub-layer is a strontium titanate layer, and the third sub-layer is a mixed material layer of titanium dioxide and graphene quantum dots.
[0057] The specific process of step S20 in this application is as follows:
[0058] Step S201: Prepare a titanium dioxide precursor solution using isopropanol, concentrated sulfuric acid, and isopropyl titanate. Spin coat the titanium dioxide precursor solution onto the first electrode layer at a speed of 100-3000 rpm for 1-10 min using a spin coater. Then, dry the solution at 10-200℃ for 10-40 min using a flat plate heater to prepare the titanium dioxide layer, which is the first sublayer mentioned above.
[0059] Step S202: Prepare a strontium titanate / isopropanol solution, and spin coat it onto the titanium dioxide layer at a speed of 100-3000 rpm for 1-10 min using a spin coater. Then, dry it at 10-200℃ for 10-40 min using a flat plate heater to prepare the strontium titanate layer, which is the second sublayer mentioned above.
[0060] In step S203, graphene quantum dots are added to an isopropanol solution and fully dissolved. Then, they are added dropwise to an isopropanol solution of titanium dioxide. The mixed solution is dispersed evenly by ultrasonic vibration and then spin-coated onto a strontium titanate layer at 2000-8000 rpm for 10-50 seconds, repeating the spin-coating 2-6 times. Finally, the mixture is dried at 10-600℃ for 10-40 minutes using a flat plate heater to prepare a mixed material layer of titanium dioxide and graphene quantum dots, namely the third sublayer mentioned above, which is the electron transport layer.
[0061] Furthermore, this application controls the mixing ratio of the graphene quantum dots and the titanium dioxide to be between 1:4 and 1:10. The presence of graphene quantum dots can reduce the reaction rate between hydroxyl groups and ammonium ions on the surface of titanium dioxide, thereby slowing down the degradation and decomposition of perovskite solar cells and further ensuring the stability of the perovskite solar cells described in this application.
[0062] Specifically, step S30 of this application involves preparing a light-absorbing layer on the third sublayer using a spin-coating method.
[0063] In addition, after step S30, the above method further includes: step S40, forming a hole transport layer on the surface of the light-absorbing layer away from the electron transport layer; and forming a second electrode layer on the surface of the hole transport layer away from the light-absorbing layer.
[0064] The specific implementation of step S40 above can be as follows: spin-coating spiro-MeOTAD on the surface of the light-absorbing layer away from the electron transport layer to prepare a dark brown-red hole transport layer, and using vacuum evaporation to form a second electrode layer on the surface of the hole transport layer away from the light-absorbing layer.
[0065] Among them, the above-mentioned spiro-MeOTAD has the molecular formula C 81 H 68 In N4O8 organic light-emitting devices and solid-state fuel-sensitized solar cells, the stable and effective hole transport material, the material of the second electrode layer is metallic gold and metallic silver.
[0066] After the perovskite solar cells were prepared using the above method, they were finally encapsulated and tested.
[0067] According to another typical embodiment of this application, a solar cell system is provided, including any of the above-described perovskite solar cells.
[0068] In the solar cell system of this application, including the aforementioned perovskite solar cell, an electron transport layer comprising multiple stacked sub-layers with sequentially increasing electronic energy levels along the direction away from the first electrode layer is provided between the first electrode layer and the light-absorbing layer, forming a "stepped" energy level structure. Compared with using titanium dioxide as the electron transport layer, this application can reduce the electron transport barrier, reduce the energy required for electron transport, improve electron transport in the perovskite solar cell structure, and thereby improve the photoelectric conversion efficiency of the perovskite solar cell.
[0069] In one embodiment of this application, the perovskite solar cell includes a first electrode layer, a first sublayer, a second sublayer, a third sublayer, a light-absorbing layer, a hole transport layer, and a second electrode layer stacked sequentially. The conversion efficiency of the perovskite solar cell obtained in this application, by selecting materials with different electronic energy levels to form the sublayers, will be further illustrated below with reference to embodiments and comparative examples.
[0070] Example 1
[0071] In the following cases, the electronic energy levels of the first electrode layer, light-absorbing layer, and hole transport layer in a perovskite solar cell are the same.
[0072] Case 1) When only a conventional perovskite solar cell structure is selected, that is, a perovskite solar cell including a first electrode layer, a titanium dioxide layer, a light-absorbing layer and a hole transport layer is selected, wherein the electronic energy level of the titanium dioxide layer is -4.18eV and its cell efficiency is 18.27%.
[0073] Case 2) When selecting a perovskite solar cell including a first electrode layer, a mixed material layer of titanium dioxide and graphene quantum dots, a light-absorbing layer and a hole transport layer, wherein the electronic energy level of the mixed material layer of titanium dioxide and graphene quantum dots is -3.95eV, the cell efficiency is 18.65%.
[0074] Case 3) When a perovskite solar cell including a first electrode layer, a titanium dioxide layer, a strontium titanate layer, a light-absorbing layer, and a hole transport layer is selected, wherein the electronic energy level of the titanium dioxide layer is -4.18 eV and the electronic energy level of the strontium titanate layer is -4.05 eV, the cell efficiency is 19.75%.
[0075] Case 4) When a perovskite solar cell is selected that includes a first electrode layer, a titanium dioxide layer, a mixed material layer of titanium dioxide and graphene quantum dots, a light-absorbing layer, and a hole transport layer, wherein the electronic energy level of the titanium dioxide layer is -4.18 eV and the electronic energy level of the mixed material layer of titanium dioxide and graphene quantum dots is -3.95 eV, the cell efficiency is 20.75%.
[0076] Case 5) When selecting a perovskite solar cell comprising a first electrode layer, a titanium dioxide layer, a strontium titanate layer, a mixed material layer of titanium dioxide and graphene quantum dots, a light-absorbing layer, and a hole transport layer, wherein the electronic energy level of the titanium dioxide layer is -4.18 eV, the electronic energy level of the strontium titanate layer is -4.05 eV, and the electronic energy level of the mixed material layer of titanium dioxide and graphene quantum dots is -3.95 eV, which is the perovskite solar cell structure described in this application, its cell efficiency is 21.83%. It can be seen that the cell efficiency of the perovskite solar cell of this application is higher than that of the perovskite solar cells in cases 1) to 4) above.
[0077] Example 2
[0078] Using the same perovskite solar cell as in Case 5 of Example 1, and with the mixing ratio of graphene quantum dots to titanium dioxide in the above-mentioned titanium dioxide and graphene quantum dot hybrid material layer being 1:4, the reaction rate of hydroxyl groups on the surface of the above-mentioned titanium dioxide with ammonium ions is 10 mol / (L×s).
[0079] Example 3
[0080] The same perovskite solar cell as in Example 1, Case 5) was used, except that when the mixing ratio of the graphene quantum dots to the titanium dioxide was 1:10, the reaction rate of the hydroxyl groups on the surface of the titanium dioxide with the ammonium ions was 8 mol / (L×s).
[0081] Example 4
[0082] The same perovskite solar cell as in Example 1, Case 5) was used, except that when the mixing ratio of the graphene quantum dots to the titanium dioxide was 1:7, the reaction rate of the hydroxyl groups on the surface of the titanium dioxide with the ammonium ions was 6 mol / (L×s).
[0083] Example 5
[0084] The perovskite solar cell uses the same material as in Example 1, Case 5), except that when the mixing ratio of the graphene quantum dots to the titanium dioxide is 1:12, the reaction rate of the hydroxyl groups on the surface of the titanium dioxide with the ammonium ions is 12 mol / (L×s).
[0085] Example 6
[0086] The perovskite solar cell uses the same material as in Example 1, Case 5), except that when the mixing ratio of the graphene quantum dots to the titanium dioxide is 1:2, the reaction rate of the hydroxyl groups on the surface of the titanium dioxide with ammonium ions is 11 mol / (L×s).
[0087] Comparing the perovskite solar cells of Examples 2 to 6, it can be seen that when the mixing ratio of the graphene quantum dots to the titanium dioxide is in the range of 1:4 to 1:10, the reaction rate of the electron transport layer and the light-absorbing layer is smaller, which achieves the purpose of suppressing the reaction between hydroxyl groups and ammonium ions.
[0088] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.
[0089] As can be seen from the above description, the embodiments of this application achieve the following technical effects:
[0090] 1) In the perovskite solar cell of this application, an electron transport layer comprising multiple stacked sub-layers with sequentially increasing electronic energy levels along the direction away from the first electrode layer is provided between the first electrode layer and the light-absorbing layer, forming a "stepped" energy level structure. Compared with using titanium dioxide as the electron transport layer, this application can reduce the electron transport barrier, reduce the energy required for electron transport, improve electron transport in the perovskite solar cell structure, and thus improve the photoelectric conversion efficiency of the perovskite solar cell.
[0091] 2) In the solar cell system of this application, including the above-mentioned perovskite solar cell, an electron transport layer comprising multiple stacked sub-layers with sequentially increasing electronic energy levels along the direction away from the first electrode layer is provided between the first electrode layer and the light-absorbing layer, forming a "stepped" energy level structure. Compared with using titanium dioxide as the electron transport layer, this application can reduce the electron transport barrier, reduce the energy required for electron transport, improve electron transport in the perovskite solar cell structure, and thereby improve the photoelectric conversion efficiency of the perovskite solar cell.
[0092] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A perovskite solar cell, characterized in that, include: First electrode layer; An electron transport layer is located on the surface of the first electrode layer. The electron transport layer includes a plurality of stacked sublayers, and the electronic energy levels of the plurality of sublayers increase sequentially in the direction away from the first electrode layer. A light-absorbing layer is located on the surface of the electron transport layer away from the first electrode layer, and the material of the light-absorbing layer includes perovskite; There are three sub-layers, namely a first sub-layer, a second sub-layer, and a third sub-layer stacked sequentially along the direction away from the first electrode layer; The first sublayer is a titanium dioxide layer, the second sublayer is a strontium titanate layer, and the third sublayer is a mixed material layer of titanium dioxide and graphene quantum dots.
2. The perovskite solar cell according to claim 1, characterized in that, The electronic energy level of the first sublayer is -4.18 eV, the electronic energy level of the second sublayer is -4.05 eV, and the electronic energy level of the third sublayer is -3.95 eV.
3. The perovskite solar cell according to claim 1, characterized in that, In the third sublayer, the mixing ratio of the graphene quantum dots to the titanium dioxide ranges from 1:4 to 1:
10.
4. The perovskite solar cell according to claim 1 or 2, characterized in that, The perovskite solar cell also includes: A hole transport layer is located on the surface of the light-absorbing layer away from the electron transport layer; The second electrode layer is located on the surface of the hole transport layer away from the light-absorbing layer.
5. The perovskite solar cell according to claim 4, characterized in that, The hole transport layer is made of spiro-MeOTAD, and the second electrode layer is made of at least one of gold and silver.
6. The perovskite solar cell according to claim 1 or 2, characterized in that, The material of the first electrode layer includes at least one of FTO conductive glass and ITO conductive glass.
7. A solar cell system, characterized in that, include: The perovskite solar cell according to any one of claims 1 to 6.
Citation Information
Patent Citations
Gradient electron transport layer perovskite solar cell and preparation method thereof
CN110400879A
Perovskite solar cell with high performance gradient electron transport layer and preparation method thereof
CN110416413A
Perovskite solar cell based on multi-layer gradient energy band electron transport layer and preparation method thereof
CN113517404A